2017
DOI: 10.1007/s12032-017-0976-4
|View full text |Cite
|
Sign up to set email alerts
|

Significance of blood neutrophil-to-lymphocyte ratio for prognostic stratification of patients with gastroesophageal junction adenocarcinoma in the era of the 8th edition of the American Joint Committee on Cancer (AJCC8) staging

Abstract: The prognosis of patients with gastroesophageal junction (GOJ) adenocarcinoma depends mainly on the clinical staging, as described by the new AJCC8 (American Joint Committee on Cancer 8th edition). Evidence suggests that peripheral blood neutrophil-to-lymphocyte ratio (NLR) may be of prognostic significance in patients with upper gastrointestinal cancers. We examined the prognostic significance of NLR in the era of the new AJCC8 staging system. In this single-centre cohort study, retrospective data on patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…A larger study (611 EJA patients) performed by Zhang et al suggested that NLR was associated with CSS, but does not play a vital role in predicting CSS of Siewert type II/III EJA [27]. Among these studies, NLR was correlated with T and N stages [24] and patients with NLR higher than 3 had a short overall survival time in stages IIB and III [22]. Therefore, it is important to further explore the predictive value of the NLR for predicting prognosis of EJA in a large-sample and multi-center study.…”
Section: Hematologic Parametersmentioning
confidence: 98%
See 2 more Smart Citations
“…A larger study (611 EJA patients) performed by Zhang et al suggested that NLR was associated with CSS, but does not play a vital role in predicting CSS of Siewert type II/III EJA [27]. Among these studies, NLR was correlated with T and N stages [24] and patients with NLR higher than 3 had a short overall survival time in stages IIB and III [22]. Therefore, it is important to further explore the predictive value of the NLR for predicting prognosis of EJA in a large-sample and multi-center study.…”
Section: Hematologic Parametersmentioning
confidence: 98%
“…As shown in Table 1, increased NLR is one of the most frequently observed markers in EJC [15][16][17][18]. With cutoff values varying from 1.84 -4.00, the NLR might act as a potential marker in predicting the survival rate of patients with EJC [19][20][21][22][23][24][25][26], especially for patients who have undergone surgery. The NLR has been found to be correlated to tumor size [21], age [22] and T stage [24].…”
Section: Hematologic Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, their median baseline NLR of 3.7 was considerably higher than found in the present study and other comparable literature which did not include metastasized tumors, indirectly suggesting that NLR may reflect the extent of dissemination. 30,31 A retrospective analysis of 117 patients with adenocarcinoma supports this theory by confirming that the NLR was an independent predictor of the discovery of peritoneal and/or metastatic disease. 32 Moreover, Conway et al recently reported an NLR ≥3 to be independently associated with early disease progression resulting in unresectable disease in patients receiving nCT for gastroesophageal junction adenocarcinoma.…”
Section: Discussionmentioning
confidence: 86%
“…32 Moreover, Conway et al recently reported an NLR ≥3 to be independently associated with early disease progression resulting in unresectable disease in patients receiving nCT for gastroesophageal junction adenocarcinoma. 30 The abovementioned findings, in addition to adequate staging and patient selection, might have played a role in our negative results as no patients with stage IV disease were included.…”
Section: Discussionmentioning
confidence: 93%